Performance of photovoltaic canarian greenhouse: A comparison study between summer and winter seasons. (1st March 2020) - Ezzaeri, K.; Fatnassi, H.; Wifaya, A.; Bazgaou, A.; Aharoune, A.; Poncet, C.; Bekkaoui, A.; Bouirden, L.
Highlights: Comparative study of the photovoltaic panels effects on the internal microclimate and tomato production during summer and winter season. Photovoltaic panels occupied 40% of the roof area does not have a significant effect on the climatic parameters during the winter season. During the summer season, the photovoltaic panels reduced the temperature inside the greenhouse and sometimes falling in the optimum range for the tomatoes growth. The photovoltaic panels does not have a significant effect on the overall yield of tomatoes. Abstract: A large-scale use of the renewable energy in agriculture has become an optimal way to successfully deal with the issues of sustainability and climate change. Recently, the integration of solar panels on the roof of the greenhouse gave birth to a new crop production system called photovoltaic greenhouse. In this paper, we investigated the shading effect of the flexible photovoltaic panels, mounted on the greenhouse roof area in the checkerboard format, on the microclimate and the tomatoes yield during the summer and winter period. This study was undertaken in a two tomato canarian greenhouses, typical of the south Mediterranean region. The results of our study showed that the photovoltaic panels covering 40% roof area of the canary type greenhouse does not have a significant effect on the climatic parameters. Additionally, during the hot period, the photovoltaic panels reduced the temperature inside the greenhouse and sometimes falling in the optimum range for the tomatoes growth. Furthermore, this occupancy rate of the photovoltaic panels does not have a significant effect on the overall yield of tomatoes.